The Influence of Workload, Work Stress, and Leadership Style on Employee Performance: The Mediating Role of Job Satisfaction at the Siak Health Center - Hamsal Hamsal; Iyoyo Dianto; Desy Mardianti; Hidayat Hidayat (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study aimed to examine the influence of workload, work stress, and leadership style on employee performance, with job satisfaction as a mediating variable at the Siak Health Center. Research Methodology: This study employed a mixed-method approach that combined quantitative and qualitative techniques. Data were collected from 306 employees using structured questionnaires measured on a 5-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among variables. Results: The findings revealed that workload and work stress have a positive but insignificant effect on employee performance, whereas leadership style has a positive and significant effect. Similarly, workload, work stress, and leadership style showed positive but insignificant effects on job satisfaction. However, job satisfaction has a positive and significant effect on employee performance. Furthermore, job satisfaction does not mediate the relationship between workload and employee performance; however, it mediates effects of work stress and leadership style on performance. Conclusions: The study concludes that leadership style and job satisfaction are key determinants of employee performance in healthcare settings, while workload and work stress do not directly reduce performance due to employees’ adaptive coping mechanisms. Limitations: This study was limited to a single healthcare institution and relied on self-reported data, which may have introduced response bias. Contributions: This study contributes the human resource management literature by providing empirical evidence of the mediating role of job satisfaction in linking workload, work stress, and leadership style to employee performance in public healthcare organizations.